Pengembangan E-Modul Pembelajaran Berdiferensiasi Berbantuan Canva dan Simplebooklet pada Materi Data dan Diagram - Nafila Ainul Azwilda; Masrurotullaily Masrurotullaily (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2026)
This research is motivated by students’ difficulties in understanding data and diagram material and the lack of teaching materials at SMPN 2 Ambulu Jember that support students’ diverse learning needs. Differentiated learning is an approach that adapts the process, content, and product of learning to students’ needs, interests, and learning profiles, enabling each student to learn optimally according to their abilities. The aim of this study is to develop a differentiated learning e-module assisted by Canva and Simplebooklet that is valid, practical, and effective for grade VII. The research method uses is the R&D method with the Hannafin and peck model through three stages: needs assessment, design, and development and implementation.  The research subjects were 34 students of grade VII C. Data collection instruments included validation sheets, student response questionnaires, and posttest questions. The results show that the e-module is highly valid (average 94.5%), practical (student response 80.95%), and effective (posttest score 73%), making it feasible as an innovative teaching material for data and diagram topics.